(untitled) (Bangladesh Journal of Infectious Diseases, 2024)
Background: The stereomorphology of renal arteries and their branches is crucial in nephrological and urological procedures, particularly in surgeries like percutaneous nephrolithotomy. Despite the clinical significance, the existing literature on the three-dimensional (3D) anatomical relationships between the renal arterial system and the renal pelvis-calyx complex remains limited and inconsistent. Objective: The objective of the study was to reveal the patterns of the three-dimensional quantitative organization of the branches of the renal artery in relation to the elements of the renal pelvis-calyx system in men. Methodology: A total of 58 corrosion specimens of male kidneys, obtained from individuals aged 22 to 75 years, were analyzed. The study employed quantitative morphological analysis to examine the extra- and intra-organ branches of the renal arteries and their relationship with the renal pelvis-calyx system. The analysis focused on the division patterns of the renal artery relative to the kidney’s excretory sectors, using 3D projection models to visualize these relationships. Results: Results revealed various patterns of arterial branching across different age groups and sectors, identifying multiple excretory sectors with distinct arterial supply configurations. Conclusion: Conclusions highlighted the clinical significance of understanding these patterns for improving preoperative planning and reducing surgical complications in nephrolithotomy and other kidney surgeries. This detailed 3D anatomical knowledge assists in tailoring surgical approaches to individual anatomical variations. Bangladesh Journal of Infectious Diseases, June 2024;11(1):59-64